Financial management and analysis - Fabozzi, Frank J. (John Wiley & Sons, Inc., 2003)
Contents: Introduction to financial management and analysis; securities and markets; financial institutions and the cost of money; introduction to derivatives; taxation; financial statements; mathematics of finance.